Diet and the Role of Altered Carbohydrate Absorption in the Treatment of Noninsulin-Dependent Diabetes Mellitus - Thomas MS Wolever (Canadian Journal of Gastroenterology)
The gastrointestinal tract has no clear role in the pathophysiology of noninsulin-dependent diabetes mellitus (NIDDM), but it may be an appropriate site for therapeutic intervention, specifically changes in diet, meal frequency and medications. Studies suggest that for patients with NIDDM, a calorie-restricted, high carbohydrate diet low in fat and rich in fibre may improve glycemic control, mitigate the risk of atherosclerosis and retard such diabetic complications as nephropathy and retinopathy. Increased meal frequency slows the rate of carbohydrate absorption, flattens blood insulin responses and reduces serum cholesterol. New therapeutic interventions, such as soluble fibre, low glycemic index foods or alpha glucosidase inhibitors, can further slow carbohydrate absorption and thus reduce secondary risks from hyperglycemia and hyperinsulinemia.